Evidence of health risks associated with prolonged standing at work for health care professionals - Mazahreh, Sam (Innovational: Journal of Nursing and Healthcare, 2024)
Standing for a long time can lead to various physical as well as psychological health related issues, such as stress, anxiety, backaches, leg cramps, fatigue, plantar fasciitis, and varicose veins, to name a few. The most affected individuals in the health care community with this problem are the nurses as well as the related staff that assists the nurses. Aim: The research paper is focused on these particular aspects of nursing health since it has a major impact of nurses everywhere. Methods: A total of 20 participants were divided into two different age groups. All participants were allowed to do standing work of six hours with 10 minutes rest breaks and 25 minutes lunch break. During the course of their activity, participants did standing work with light manual tasks on the workbench. Other tasks included reading, frequent computer work. For the ease of the participants, any forceful exertion was not done. During the rest period, comfortable rest chair was provided to the participants for improving the accuracy of the results. Results: Problems were mainly physical and psychological health issues, as well as poor quality health care that was delivered to the patients. It has been identified that when nurses do a 12-hour shift, the chances of patient error increases with that, and the quality of work gets compromised. By accompanying the techniques of postural stability and subjective evaluation of discomfort of individuals after 40 minutes of standing work, the study showed evidence suggesting long-term neuromuscular fatigue and abnormal physiological effect associated with health care professionals that constantly stand while working.